Vegetable biocorrectors influence on the moisture state in functional purpose flour products - N. S. Rodionova (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2019)
The development of new technological solutions in the field of daily consumed food products, which have a directed corrective impact on the nutritional status of the human body and an extended shelf life is an important and urgent task. One of the alternative solutions to the problem faced is the introduction of flour products (crackers, biscuits, bread), enriched with biologically active substances of plant origin into the daily ration. They are economically accessible to the general population and suitable for sale in a network format, due to significant shelf life. Experimental studies to assess the effect of introduced biologically active substances on the shelf life of flour products through the study of changes in the content and ratio of various forms of bound moisture were carried out in the work. The study of moisture state in flour products was carried out by the method of differential thermal analysis using a synchronous thermal analysis device using thermogravimetry, differential scanning calorimetry and non-isothermal kinetics. The objects of research were samples of flour products containing the composition of partially defatted wheat germ flour "Vitazar" and wheat bran, which were additionally added with seaweed powder, soy protein isolate, pea protein isolate, black cumin seed flour. Samples of flour products (biscuits) made according to traditional technology served as controls. A quantitative assessment of the ratio of moisture fractions with various bonds was carried out by the methods of thermogravimetry, differential scanning calorimetry and non-isothermal kinetics. The ranges of endothermic effects, indicating stepwise moisture removal, in accordance with the forms and energy of its connection with the experimental samples biopolymers were identified in the work. Comparison of thermal effects characteristics recorded in the process of thermolysis of flour products samples, allows us to state an increase in the chemically bound moisture share in the test samples, as compared with the control sample and, as a result, an increase in shelf life.